The Motives of Lithuanian Inhabitants to Enrol in Kaunas Self-defence Battalions in Summer and Autumn 1941 - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2012)
This article examines the biographical data of Lithuanian inhabitants who served during the Nazi occupation (1941-1944) in Kaunas National Labour Protection battalion (TDA), and in the Auxiliary Police Service (PPT) 1st and 2nd battalions, formed in August 1941 on TDA’s basis. The number of people they killed distinguishes these battalions from other Lithuanian self-defence units. Throughout the history of Lithuania no other military structure killed as many innocent people as they did. Among other reasons, these battalions were chosen because more data on them survived. The goal of the article is to answer the question on what motivated Lithuanian inhabitants to join these battalions. This historical cognitive question is also relevant because it was not researched in the works of other historians on the Nazi period in Lithuania. The clues about the motives for joining these battalions can only be evaluated as hypotheses, the validity of which should be either confirmed or denied. The facts on the battalions’ participation in exterminating Jews and other groups of people leads one to the impression that Lithuanians joined these as well as other Nazi battalions with the incentive to murder. After completing the research on the biographical data it was ascertained that the opinion about joining for the motive of murder was not correct. This is confirmed by the circumstance that when joining the self-defence battalions, people were not aware that they would have to take part in the extermination operations of Jews and other groups. The troops were divided into four groups according to their motives for enrolling in military structures: 1) Patriots; 2) Unemployed and other jobseekers; 3) victims; 4) the insecure. Such classification is not strict, i.e. some persons can be attributed to several groups. By analysing the biographical facts of the troops who served in these battalions it was established that their motive for joining them was their patriotic inclinations, desire to have a job and receive payment, ambition to avenge the wrongs of the Soviet regime, willingness to avoid punishment for joining the Soviet regime, deportation to labour camps in Germany and to escape the fate of prisoners of war. In determining these inner motives, not only historical knowledge, but also knowledge of other science disciplines was used. The analysis of biographical data suggests that the inhabitants of the land who joined the self-defence units were motivated not by one, but rather several motives. They saw Kaunas TDA, 1st and 2nd PPT battalions as a means to satisfy their own inner motives. These motives led them to enrol in these military units in summer and autumn of 1941.